Perancanga Sistem Informasi Perpustakaan SMA Negeri 1 Danau Kembar - Meri Afliyanti; Zulhendra Zulhendra; Denny Kurniadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
Library management at SMA country 1 twin lake in this time not yet optimal and not based on computerization. aim from library information system sma country 1 twin lake based on web is a information system that designed to give and optimize operator performance. in give service to library member, in service search book, loaning service and library book return, accessinged according to online. this application planning uses language java with idea netbeans and place to keep database that is mysql. program implementation at require medium shaped computer that integration webserver. implementation result from information system library this is library operator can make recapitulation member report, book total report, fine report, loaning report and return. Keyword: Library Information System, Java, Mysql And Idea Netbeans.